2021
DOI: 10.3390/jcm10204793
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology and Management of Hemorrhagic Shock in the Polytrauma Patient

Abstract: The recognition and management of life-threatening hemorrhage in the polytrauma patient poses several challenges to prehospital rescue personnel and hospital providers. First, identification of acute blood loss and the magnitude of lost volume after torso injury may not be readily apparent in the field. Because of the expression of highly effective physiological mechanisms that compensate for a sudden decrease in circulatory volume, a polytrauma patient with a significant blood loss may appear normal during ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 201 publications
(218 reference statements)
0
15
0
3
Order By: Relevance
“…After this threshold the O2ER reaches a plateau. If blood loss continues the compensatory mechanism will be overcome and VO2 will be dependent on flow [16][17][18][19]. Depending on the amount of blood lost, there are four stages of hemorrhagic shock and fluid resuscitation is based on these 4 stages.…”
Section: Pathophysiology Pathways In Hemorrhagic Shockmentioning
confidence: 99%
“…After this threshold the O2ER reaches a plateau. If blood loss continues the compensatory mechanism will be overcome and VO2 will be dependent on flow [16][17][18][19]. Depending on the amount of blood lost, there are four stages of hemorrhagic shock and fluid resuscitation is based on these 4 stages.…”
Section: Pathophysiology Pathways In Hemorrhagic Shockmentioning
confidence: 99%
“…1,2 Moreover, hemorrhagic shock (HS) is the most potentially preventable cause related to deaths after trauma, occurring early before arriving at the hospital, and associated with coagulopathy, microcirculation dysfunction, and prominent inflammatory response. 3,4 Several studies demonstrated the development of traumainduced secondary cardiac injury (TISCI) and dysfunction, independent of direct heart trauma, due to myocardial ischemia and ischemia-reperfusion injury, prompted by cardiomyocyte death and microvascular injury, and leading to increased morbidity and risk of death. 5,6 The analysis of myocardial deformation or strain by speckle tracking echocardiography (STE) is a novel noninvasive imaging tool to measure cardiac performance, and it has been shown to have superior sensitivity, reproducibility, accuracy, and predicted power to cardiovascular (CV) events when compared with established methods such as left ventricle (LV) ejection fraction.…”
mentioning
confidence: 99%
“…1,2 O choque hemorrágico (CH), decorrente do trauma, é considerado uma causa de óbito evitável, ocorrendo precocemente antes da chegada ao hospital, e está associado à coagulopatia, disfunção da microcirculação e proeminente resposta inflamatória. 3,4 Vários estudos demonstraram o desenvolvimento de lesão e/ou disfunção secundária cardíaca relacionada ao trauma (ICRT) independente de traumatismo cardíaco direto, tendo como principais mecanismos fisiopatológicos isquemia miocárdica, lesão de isquemia-reperfusão e liberação de marcadores inflamatórios, ocasionando lesão microvascular e morte de cardiomiócitos, determinando um aumento da morbidade e mortalidade. [5][6][7][8] A presença da disfunção cardíaca está diretamente relacionada com a mortalidade, o que torna necessária melhor compreensão e determinação temporal das alterações na microestrutura miocárdica.…”
Section: Lista De Figurasunclassified
“…Uma hora após o estabelecimento do estado de choque hemorrágico grave, houve uma redução estatisticamente significativa no conteúdo de oxigênio no sangue venoso misto (6,2 [5,8, 7,2] vs. 1,8 [1,3,3,4] mL/dL), p = 0,018) e da oferta de oxigênio (48,1 [42,4,51,3] vs. 20,8 [17,8,26,5] mL/min, p = 0,018), com aumento possivelmente compensatório na extração de oxigênio (42,6 [39,8, 48,4] b A comparação entre os tempos de estudo experimental para cada variável foi feita por meio do teste de Wilcoxon. * P < 0,05 foi considerado significativo.…”
Section: Variáveis Microdinâmicas De Oxigenação Tissularunclassified
See 1 more Smart Citation